Kilka uwag o nowym kodeksie karnym - Patryas, Wojciech (Wydział Prawa i Administracji UAM, 1997)
The article is an attempt to take a critical look on certain constructions inherent to the new penal code. Still, its article 1 raises reservation when it forces into recognition of omissions as being acts - just like corresponding article of previous code did it. The new article 2 of the code leads also to various complications through its definition of a responsibility for so-called offences by omission with criminal results. Doubts also arise from constructions of factual forms of offence foreseen in the code, and this concerns both construction of prepetration of a criminal offence and constructions of preparation for a crime and of incitement to crime.
Some remarks on new penal code